Oligomerization of ethylene promoted by methylaluminoxane activated arylchalcogenyl‐sulfonate nickel(II) complexes. (26th December 2022) - da Costa, Miriã Terra; Lopes, Eric Francis; Oliboni, Robson S.; Lüdtke, Diogo S.; Casagrande, Osvaldo L.; Stieler, Rafael
Abstract : A new synthetic route to arylchalcogenyl‐sulfonate ligands (E, SO) (E = Se, S) and the synthesis and ethylene reactivity of two new nickel complexes [NiCl(py)(E, SO)] (Ni1, E = Se; Ni2, E = S) are reported. The minimum energy structures of the complexes were determined by density functional theory (DFT) calculations. For both compounds, the triplet and singlet 1 structures (with Cl trans to chalcogen) are higher in energy compared with singlet 2 (with Cl cis to chalcogen). Under initial catalytic condition (MAO, [Al/Ni] = 300, time = 20 min, T  = 30°C) complex Ni1 oligomerizes ethylene with turnover frequencies (TOF) of 32.6 × 10 3 (mol ethylene) (mol Ni) −1 (h) −1 with 81.3% of 1‐butene production. The use of different cocatalyst systems (MAO/TMA or MAO/TiBA in an equimolar ratio) led to lower activities and poor selectivity for 1‐C4 . Under optimized reaction conditions (MAO, [Al/Ni] = 600, time = 20 min, T  = 30°C), the phenylthionyl complex Ni2 was 1.7 times more active than the phenylselenyl analog, with TOF of 72.3 × 10 3 (mol ethylene) (mol Ni) −1 (h) −1 with 84.3% of 1‐butene selectivity. DFT calculations suggest that the lowest lowest unoccupied molecular orbital (LUMO) energy and highest natural charge at the Ni center could be associated to the higher activity of Ni2 compared with the phenylselenyl analog Ni1 . Abstract : In the presence of MAO complexes Ni1 and Ni2 were able to oligomerize ethylene with higher selectivity for 1‐butene. The lowest LUMO energy and highest nickel natural charge in Ni2 lead to higher activity of Ni2 in comparison to Ni1 .